2014
DOI: 10.1186/1471-2482-14-25
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall reconstruction with components separation and mesh reinforcement in complex hernia repair

Abstract: BackgroundAbdominal closure in the presence of enterocutaneous fistula, stoma or infection can be challenging. A single-surgeon’s experience of performing components separation abdominal reconstruction and reinforcement with mesh in the difficult abdomen is presented.MethodsMedical records from patients undergoing components separation and reinforcement with hernia mesh at Royal Liverpool Hospital from 2009 to 2012 were reviewed. Patients were classified by the Ventral Hernia Working Group (VHWG) grading syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 13 publications
2
37
0
4
Order By: Relevance
“…The mesh reinforcement is controversially discussed for reasons of costs. The recurrence rate is (in the available non-controlled studies) reported comparably high (10-35%) and it is higher without mesh reinforcement [57][58][59][60][61][62][63][64][65]. The method can be performed in principal laparoscopically, too [66][67][68] and with advantages in obese patients [69].…”
Section: Components Separationmentioning
confidence: 99%
“…The mesh reinforcement is controversially discussed for reasons of costs. The recurrence rate is (in the available non-controlled studies) reported comparably high (10-35%) and it is higher without mesh reinforcement [57][58][59][60][61][62][63][64][65]. The method can be performed in principal laparoscopically, too [66][67][68] and with advantages in obese patients [69].…”
Section: Components Separationmentioning
confidence: 99%
“…A total of 601 patients were included, with an average follow‐up of 26.7 months. Follow‐up was performed by clinical assessment in five studies , a combination of clinical assessment and telephone interviews in three studies and was not defined in seven studies . None of the studies gave a clear definition of hernia recurrence and only one differentiated between hernia and bulge .…”
Section: Resultsmentioning
confidence: 99%
“…Su empleo permite la medialización de los bordes del defecto con cierre directo de la fascia (sin dejar un puente protésico), lo que disminuye el riesgo de recidiva. Dada la fragilidad lateral de la pared en este tipo de correcciones favorecida por la presencia de varios orificios de trocares laterales, se utiliza el remanente de la prótesis biosintética para el refuerzo de esta región más débil 15 . En la corrección de las HVCC el riesgo de infecciones de la herida quirúrgica es más elevado, por la presencia de factores de riesgo como la prótesis (cuerpo extraño), la disección amplia en las técnicas de separación de componentes, el tipo IV de hernia incisional categoría tipo IV de la clasificación VHWG, paciente ASA 3 y padecimiento de obesidad mórbida (IMC de 40 kg/m 2 ) 16 .…”
Section: Discussionunclassified